The Effective Factors in the Accuracy of 3D Printers in Dentistry:A Systematic Review - Sayed Shojaedin Shayegh; Maryam Jahangiri (Mashhad University of Medical Sciences, 2024)
Background: The use of digital technology in dentistry has gained prominence over the past decade and 3D dental printing has become popular in various fields of dentistry. Very few studies have investigated the factors that impact a precise three-dimensional print. In this review, we examine the factors influencing the accuracy of dental prints.Methods and Materials: A comprehensive search was conducted across databases such as PubMed, Google scholar, Scopus, Springer Link, Science Direct, and Wiley using terms related to "Digital dentistry", "3D printer", "CAD/CAM", "Stereolithography" and "Accuracy". We retrieved studies published from January 2017 to February 2024 in English or Persian language.Results: A total of 800 studies were initially identified and 70 studies were screened by title and abstract. Finally, 22 studies were qualified for full text review. The findings showed that the main effective factors fall in to one of the four categories: printer type, material combinations, and factors during and after the printing process.Conclusion: Various factors have an effect on the accuracy of printers and identifying these factors increases the accuracy, dimension and color stability of the printed samples. Regarding the factors during printing, the angle of the print, the layer thickness of the printed samples and the curing process affect the accuracy of the prints. Regarding the material combinations, the powder size used in powder-based and resin type in resin-based printers are recognized as influential factors. The post-printing factors also include the storage method and duration, which has a significant effect on dimensional stability.